Legal Protection for Heirs with Non-Fungible Token Heritage Objects - Erika Nur Syarifah Daulay; Akhmad Budi Cahyono (Dinasti Research, 2025)
The development of digital technology has introduced Non-Fungible Tokens (NFT) as a form of digital asset that has its own economic value and uniqueness. This opens up the potential for NFTs as objects of inheritance, however the traditional inheritance law system in Indonesia has not fully accommodated non-physical entities such as NFTs, especially due to unclear regulations regarding the transfer of rights to these assets after the death of the owner. This article discusses legal protection for heirs with NFT inheritance objects. This research uses normative or doctrinaire research methods using secondary data and a comparative legal approach, which involves analysis of relevant laws and regulations and NFT practices in several jurisdictions that have recognized the existence of NFTs. Based on the research results, NFTs can be inherited through a general will made by a notary, olographic, or private. However, the main challenge is access to digital wallets that store NFTs and are at risk of being lost if there is not sufficient technical information regarding access. To overcome this, inheritance planning with a dead's man switch mechanism in smart contracts can enable the automatic transfer of NFTs to heirs. However, legal recognition of this mechanism is still limited. This research highlights the need for clearer regulations and legal updates in Indonesia regarding digital asset inheritance, to provide legal certainty for owners and heirs as technology develops. It is hoped that the results of this research can contribute to the formulation of clearer regulations and provide adequate legal protection for heirs and heirs who own digital assets in Indonesia.